Co‐targeting the PI3K/mTOR and JAK2 signalling pathways produces synergistic activity against myeloproliferative neoplasms. Issue 11 (17th November 2013) - Bartalucci, Niccolò; Tozzi, Lorenzo; Bogani, Costanza; Martinelli, Serena; Rotunno, Giada; Villeval, Jean‐Luc; Vannucchi, Alessandro M.
Abstract Aberrant JAK2 signalling plays a central role in myeloproliferative neoplasms (MPN). JAK2 inhibitors have proven to be clinically efficacious, however, they are not mutation‐specific and competent enough to suppress neoplastic clonal haematopoiesis. We hypothesized that, by simultaneously targeting multiple activated signalling pathways, MPN could be more effectively treated. To this end we investigated the efficacy of BEZ235, a dual PI3K/mTOR inhibitor, alone and in combination with the JAK1/JAK2 inhibitor ruxolitinib, in different preclinical models of MPN. Single‐agent BEZ235 inhibited the proliferation and induced cell cycle arrest and apoptosis of mouse and human JAK2V617F mutated cell lines at concentrations significantly lower than those required to inhibit the wild‐type counterpart, and preferentially prevented colony formation from JAK2V617F knock‐in mice and patients' progenitor cells compared with normal ones. Co‐treatment of BEZ235 and ruxolitinib produced significant synergism in all these in‐vitro models. Co‐treatment was also more effective than single drugs in reducing the extent of disease and prolonging survival of immunodeficient mice injected with JAK2V617F‐mutated Ba/F3‐EPOR cells and in reducing spleen size, decreasing reticulocyte count and improving spleen histopathology in conditional JAK2V617F knock‐in mice. In conclusion, combined inhibition of PI3K/mTOR and JAK2 signalling may represent a novel therapeutic strategy in MPN.